On the influence of tooling behaviour over axial shortening mechanisms in linear friction welding of titanium alloys and modelling plasticisation effects. (February 2021) - Lachowicz, D.S.; Bennett, C.; Axinte, D.A.; Lowth, S.; Walpole, A.; Hannon, C.
Abstract: Linear Friction Welding (LFW) has often been studied with the principal goal of describing complex physical interactions at the weld interface. Most published research has focused on the LFW process itself and under many assumptions: simplified welding geometries, over-constrained and rigid assemblies, and idealised clamping conditions. Equipment and tooling characteristics must be considered alongside the process itself for a more comprehensive understanding of LFW. The following study is aimed at addressing observed unaccounted variance in process outputs by investigating Ti6Al4V alloy welds processed under uniform conditions. A method for machine characterisation and a new experimental data analysis workflow is proposed, based on data processing techniques in spectral, temporal, and spatial domains. Research findings presented in this paper describe new plasticisation phenomena which accompany axial shortening in LFW welds. A new kinematic model is proposed, explaining macroscopic interactions at the contact interface. It allows for identification of shortening behaviour prevailing in the process, estimation of relative shape thickness of the thermo-mechanically affected zone, as well as potential for macroscopic misalignment between two joint substrates. Post-weld metrological investigations indicate a link between joint misalignment and effects observed, suggesting that tooling could influence weld shortening behaviour by disturbing planarity at the contact interface. Graphical abstract: Image 1 Highlights: Repeatability study on welds shown variability in workpiece alignment. Multi-domain analysis of weld outputs captured new process phenomena. Two models of upsetting behaviour were identified based on weld output signals. Upsetting behaviour is likely linked with relative curvature of the plasticised zone. Proposed upsetting model allows for prediction of weld interface tilting pattern.